Analisis Faktor-Faktor Preferensi Etnis Tionghoa Terhadap Bank Syariah di Indonesia - Yurita Sari; Ujang Sumarwan; M Nadratuzzaman Hosen (Department of Islamic Economics, IPB University, 2015)
The research aimed to develop and to test the consistency of the relationship between preference factrs of Chinese Ethnic towards Islamic Banks in Indonesia. According to previous research, customer’s internal and external factors as well as marketing strategy of the Islamic Banks are the main reason behind their decisions to become Islamic Banks’ customers. However, some of the previous researches have also shown inconsistent result in which it is stated that the religious factor is the main reason for Chinese Ethnic to choose Islamic Banks, whereas some other research concluded that religion has nothing to do with the decision to become customer in Islamic Banks.In line with the purpose of the research is to analyze how far the factors mentioned above could influence the preference of people with Chinese Ethnicity towards Islamic Banks. The approach used in this research is survey method. Sumarwan (2011) explains that survey is a design of a research which collects data from some respondents that are selected from a population. The sample of this research is Indonesian Chinese Ethnics, including the Muslim ones and also include those who are already a customer in Islamic Banks as well as those who are not. This study specifically analyzes perception attribute variable such as location, higher return, quality service, Islamic bank’s reputation and image, product features, marketing, and teknology; and also environment variable, personal variable, culture variable, and lastly preference variable of the Chinese ethnics towards Islamic Banks in Indonesia by using AIDA (awareness, interest, desire) model approach. The data is analyzed by using SEM (structural equation model) technique.An interesting phenomenon of the research is that Islamic Banks use Islamic principles which prohibited the act of Riba’, while the Chinese Ethnic customers and the prospective customers also considering the same thing. Most of Chinese Ethnics are Buddhist, Christian, and Catholic which prohibited interests in banking system.The result of this study concluded that the level of knowledge of Chinese Ethnics that are not yet a customer towards Islamic Banks is lower than the knowledge level of Muslim Chinese Ethnics who are already a customer in Islamic Banks. With AIDA model, it is found that environment variable which consists of social and culture has significant influence towards atribute perception and also towards other AIDA variables such as Awareness, interest and desire.